The influence of metacognition monitoring on L2 Chinese audiovisual reading comprehension - Wang, Yamin; Hu, Jingying; An, Zhuoma; Li, Chaoran; Zhao, Yang (Frontiers in Psychology, 2023)
Metacognition monitoring is the ability to evaluate the cognitive process actively. L2 learners with high metacognition monitoring ability can better monitor reading processes and outcomes consciously, thus facilitating self-regulated learning and improving reading efficiency. Previous studies mostly used offline self-reports to examine the metacognition monitoring in static text reading by L2 learners. This study investigated the effects of different indicators of metacognition monitoring on L2 Chinese audiovisual comprehension by online confidence judgment and audiovisual comprehension tasks. Target measures of metacognition monitoring included absolute calibration accuracy based on video or test and relative calibration accuracy measured by Gamma or Spearman correlation coefficient. 38 intermediate-advanced Chinese learners participated in the study. Multiple regression analysis showed three main results. First, absolute calibration accuracy can significantly predict L2 Chinese audiovisual comprehension, while relative calibration accuracy has no significant effect. Second, the predictive effect of video-based absolute calibration accuracy is affected by the video difficulty, that is, the greater the video difficulty, the greater the impact on the performance of audiovisual comprehension. Third, the predictive effect of test-based absolute calibration accuracy is influenced by the language proficiency, specifically, the higher the L2 Chinese proficiency, the stronger the prediction on the performance of audiovisual comprehension. These results support a multidimensional view of metacognition monitoring by specifying how different indicators of metacognition monitoring may predict L2 Chinese audiovisual comprehension. The findings have important pedagogical implications for strategy training of metacognition monitoring and point to the necessity to take task difficulty and individual differences among learners into full consideration.